Energy, exergy, exergoeconomic, and exergoenvironmental analysis of an innovative solar-geothermal-gas driven polygeneration system for combined power, hydrogen, hot water, and freshwater production. (June 2022) - Khoshgoftar Manesh, M.H.; Mousavi Rabeti, S.A.; Nourpour, M.; Said, Z.
Highlights: A Polygeneration system including power, fresh water, hydrogen and hot water production is proposed. Hybridization of solar, geothermal and natural gas has been used. The thermal efficiency of the whole system during the year is calculated as an average of 23.87%. The LCOA is calculated 0.144 /kWh. Abstract: In the present work, an innovative solar-geothermal-natural gas-driven polygenration system is presented. It consists of using organic Rankine cycle, Internal Combustion Engine, Polymer Electrolyte Membrane, and Humidification-Dehumidification desalination plant to produce power, hydrogen, hot water, and freshwater. Energy, Exergy, Exergoeconomic, and Exergoenvironmental (4E) analyses have been performed for the proposed system. 4E analyses can provide a comprehensive overview of the proposed system. In addition, sensitivity analysis for the system's main parameters has been done to evaluate the system. Also, nine organic fluids were used and compared based on 4E analyses. The results show that energy and exergy efficiencies and total annual cost and environmental impacts of the system are 23.87%, 28.21%, 0.144 /kWh, and 0.024 Pts/kWh. Also, the average production of freshwater is 4.67 m 3 /day, and the production of hydrogen and hot water is estimated at 1.85 kg/h and 1.31 kg/s, respectively. R141b is the best fluid for the organic Rankine section.